Altered rainfall patterns increase forb abundance and richness in native tallgrass prairie - Jones, S. K.; Collins, S. L.; Blair, John M.; Smith, M. D.; Knapp, A. K. (My University, 2016)
Models predict that precipitation variability will increase with climate change. We used a 15-year precipitation manipulation experiment to determine if altering the timing and amount of growing season rainfall will impact plant community structure in annually burned, native tallgrass prairie. The altered precipitation treatment maintained the same total growing season precipitation as the ambient precipitation treatment, but received a rainfall regime of fewer, larger rain events, and longer intervals between events each growing season. Although this change in precipitation regime significantly lowered mean soil water content, overall this plant community was remarkably resistant to altered precipitation with species composition relatively stable over time. However, we found significantly higher forb cover and richness and slightly lower grass cover on average with altered precipitation, but the forb responses were manifest only after a ten-year lag period. Thus, although community structure in this grassland is relatively resistant to this type of altered precipitation regime, forb abundance in native tallgrass prairie may increase in a future characterized by increased growing season precipitation variability.
Citation: Jones, S. K., Collins, S. L., Blair, J. M., Smith, M. D., & Knapp, A. K. (2016). Altered rainfall patterns increase forb abundance and richness in native tallgrass prairie. Scientific Reports, 6, 10. doi:10.1038/srep20120
Keywords: Plant Community; Precipitation Variability; Terrestrial Ecosystems; Desert Grassland; Aboveground Productivity; Species Richness